1998
DOI: 10.4319/lo.1998.43.6.1344
|View full text |Cite
|
Sign up to set email alerts
|

The trophic dynamics of riverine bacterioplankton: Relationships among substrate availability, ectoenzyme kinetics, and growth

Abstract: The role of dissolved organic matter (DOM) in the trophic dynamics of aquatic systems is difficult to study. One approach is to focus on the activity of the extracellular enzyme systems that heterotrophic bacteria use to obtain nutrients from DOM. These data are easy to acquire, but difficult to interpret, because we lack general models that relate these activities to the two sides of the trophic reaction: the DOM pool and bacterial production. To address this gap, we collected water samples from the Maumee Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 0 publications
8
62
0
Order By: Relevance
“…In the water of the Słupia River, the maxima of the activity of lipases were observed in spring and fall. Similar results were obtained by Foreman et al (1998) in the Maumee River (northwest Ohio) and Boon (1990) in the Kiewa River (south-eastern Australia). The higher activity of lipases observed in spring in the Słupia River could have resulted from the considerable amounts of allochthonous lipids flowing into the water together with the snow melt, while an increased level of the activity of lipases in fall could have been related to heavy rainfall and increased mortality of phytoplankton and zooplankton which brings considerable amounts of lipids into the water (Arts et al 1992).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the water of the Słupia River, the maxima of the activity of lipases were observed in spring and fall. Similar results were obtained by Foreman et al (1998) in the Maumee River (northwest Ohio) and Boon (1990) in the Kiewa River (south-eastern Australia). The higher activity of lipases observed in spring in the Słupia River could have resulted from the considerable amounts of allochthonous lipids flowing into the water together with the snow melt, while an increased level of the activity of lipases in fall could have been related to heavy rainfall and increased mortality of phytoplankton and zooplankton which brings considerable amounts of lipids into the water (Arts et al 1992).…”
Section: Discussionsupporting
confidence: 83%
“…The mean lipase activity of the aerobic isolates from a river is 5 × 10 -11 μM MUF min -1 and anaerobic isolates 3 × 10 -13 μM MUF min -1 . The activity of lipases in the water of the Słupia River was low as compared to other rivers (Jones, Lock 1993;Boon 1990;Foreman et al 1998). This low activity of lipid-hydrolyzing enzymes might be due to the fact that in the study area only 5 -8% of heterotrophic bacteria had lipolytic properties.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The low amount of consumed oxygen could be explained by the fact that tannin depressed enzyme activities and had a little effect on productivity, driving down growth efficiency of microorganisms (Foreman et al, 1998). Another study on tannic acid interaction showed that this polyphenol might lead to the formation of both soluble and insoluble aggregates with proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The rate-limiting steps in the mineralization of organic matter could be enzyme-induced hydrolysis of macromolecules (Keyhani and Roseman, 1997;Foreman et al, 1998;Grossart et al, 1998). Enzymes mediate a wide variety of biogeochemical chemical reactions, and have been linked to nutrients cycling in soils/sediments (Burns, 1986;Pant and Warman, 2000;Furlan and Pant, 2006) and aquatic systems (Pant et al, 2002).…”
Section: Introductionmentioning
confidence: 99%